Cryptosporidiosis, an Uncommon Complication after Allogeneic Stem-Cell Transplantation - Edwige Boulet; Carlos Graux; Anne Sonet; Julien Depaus; Hélène Vellemans; Marc André; Caroline Fervaille; Elodie Collinge (Case Reports in Oncology, 2023)
Parasitic infections by Cryptosporidium species are rare but can be life-threatening disease after allogeneic stem-cell transplantation (allo-SCT). Here, we reported a case of cryptosporidiosis occurring after a reduced-intensity conditioning and allo-SCT in a 64-year-old farmer with diffuse large B-cell lymphoma. Around day 70 after allo-SCT, he presented with diarrhea attributed to graft-versus-host disease (GvHD) and was treated with immunosuppressive therapy. Due to the patient’s worsening clinical condition, a biopsy review was performed, revealing evidence of cryptosporidiosis. Therefore, immunosuppressive therapy was progressively decreased, and antimicrobial therapy including paromomycin and azithromycin was initiated. Following an increase in diarrhea, a second-line treatment with nitazoxanide was administered, resulting in gradual improvement of symptoms. However, recurrence of cryptosporidiosis occurred despite treatment with paromomycin 6 months after transplant and after an episode of GvHD recurrence and colic cytomegalovirus reactivation. Antiparasitic treatment was stopped and azithromycin and rifaximine were started. Immunosuppressive therapy was also reduced. The good clinical evolution allowed for the cessation of all medications. In conclusion, Cryptosporidium infection can complicate allo-SCT and be mistaken for GvHD at the clinical and histologic levels. Early and accurate diagnosis is all the more important as the therapeutic approach for the two conditions is opposite: reduction versus intensification of immunosuppressive therapy. Nitazoxanide, paromomycin, and azithromycin are the first therapeutic options.